Soluble Mucosal Addressin Cell Adhesion Molecule 1 and Retinoic Acid are Potential Tools for Therapeutic Drug Monitoring in Patients with Inflammatory Bowel Disease Treated with Vedolizumab: A Proof of Concept Study. (31st May 2018) - Paul, Stephane; Williet, Nicolas; Di Bernado, Thomas; Berger, Anne-Emmanuelle; Boschetti, Gilles; Filippi, Jerome; Del Tedesco, Emilie; Nancey, Stephane; Flourie, Bernard; Roblin, Xavier
Abstract: Background and Aims: Vedolizumab [VDZ], a humanized monoclonal antibody targeting α4β7 integrin, is effective in induction and maintenance therapy in patients with inflammatory bowel disease [IBD] who have not adequately responded to standard therapies, and high vedolizumab trough levels [VTLs] have been associated with clinical remission. The α4β7 integrin binds to endothelial MAdCAM-1 and is upregulated by retinoic acid [RA]. The aim of this study was to determine the relationships between soluble MAdCAM-1 [sMAdCAM-1] and RA concentrations during clinical remission with VDZ maintenance therapy. Methods: In a retrospective study performed in IBD patients treated with VDZ, we measured VTL, sMAdCAM-1 and RA concentrations. Results: Among the 62 included patients [38 Crohn's disease], 24 relapsed and 38 stayed in remission from Weeks 10 to 30 after VDZ initiation. During this maintenance therapy, the median values of VTLs and RA were 15.4 µg/mL and 0.97 ng/mL, respectively, whereas sMAdCAM-1 was undetectable [<0.41 ng/mL] in 67.3% of samples. The positive predictive value [PPV] of undetectable sMAdCAM-1 for clinical remission was 80.0%, with a corresponding sensitivity of 74.6%. On multivariate analysis, undetectable sMAdCAM-1 and high VTLs [>19 µg/mL] were independently associated with clinical remission [OR = 7.5, p = 0.006 and OR = 2.2, p = 0.045, respectively]. The combination of sMAdCAM-1 < 0.41 ng/mL and VTL > 19 µg/mL was the best pharmacokinetic profile, with a PPV of 95.2%. Median values of sMAdCAM-1 and RA were significantly higher [ p = 0.0001] before VDZ therapy than during the follow-up [sMAdCAM-1: 40.5 vs < 0.41 ng/mL; RA: 1.7 vs 0.97 ng/mL]. Only RA > 1.86 ng/mL before VDZ therapy was predictive of clinical remission during the follow-up (Area Under a Receiver Operating Characteristic curve [AUROC] = 80.7%). Conclusions: Undetectable sMAdCAM-1 appears strongly associated with clinical remission during VDZ maintenance therapy. Combination of undetectable sMAdCAM-1 with high VTL is also potentially interesting for therapeutic drug monitoring. Baseline RA concentrations are predictive of clinical remission. These findings need to be confirmed in further prospective studies.